ANALISIS PENGARUH SENSUAL MARKETING TERHADAP MINAT BELI PADA PRODUK CLOTHING LINE â€œBERAKâ€ DI INSTAGRAM - Jimmy Ary Pratama; Fitroh Adhilla (Jurnal Fokus Manajemen Bisnis, 2016)
This research is to find out whether there is a significant influence between sensual marketing strategies that are triggered by a model, body language, and nature how to communicate with buying interest in "Shit" clothing line products in the media instagram, both partially and simultaneously. The population of this research is the students of private universities in the city Yogyakarta has never seen a display of defecated Instagram. Samples in research this amounted to 80 respondents where the determination using accidental techniques sampling and purposive sampling. Testing using statistical tests multiple linear regression analysis. Partially, the statistical test used is a test t and simultaneously using the F test. Data collection techniques with questionnaire distribution. As for testing the instrument uses test validity and reliability. From the analysis it can be concluded that partially sensual strategy marketing which consists of model, body language, and method variables communicating significantly. Whereas simultaneously the strategy sensual marketing also has a significant influence on buying interest.